Analysis of Satria Vocational High School Digital Campaign Strategy with Instagram Social Media - Revalina Hadisah; Safiani A. Faaroek; Resman Muharul Tambunan; Heriyanti (Formosa Journal of Applied Sciences, 2022)
Social media is a powerful tool for companies to communicate with customers effectively, share each other contents, understand customer needs, and build trust among customers. Some various features provided by social media also encourage business doers and educational institutions to create new marketing strategies such as social media campaigns. This study aims to determine the methods used by SMK Satria in digital campaigns on the @smksatriajkt Instagram and how to carry out the strategy in terms of content, promotion and visualization of activities. This research method uses descriptive qualitative research by developing a constructivism paradigm approach. The results of this study show that: (1) The digital content of SMK Satria represents a simple, yet informative and communicative visualization in each post. (2) The promotion aspect of SMK Satria through their Instagram account is quite innovative and it can be seen from posted contents which associated with certain artists. (3) The visualization of SMK Satria digital campaigns has been maximized as seen from the use of features on Instagram, specifically for the PPDB digital campaigns.